Pengaruh Kebutuhan Motivasi Ekstrinsik, Dukungan Rekan Kerja, dan Religiusitas terhadap Kepuasan Kerja pada Pegawai Kantor Kementerian Agama Kabupaten Padang Pariaman - utri (JURNAL AKUNTANSI DAN MANAJEMEN, 2023)
Job satisfaction is closely related to the condition of employees and the company which is associated with increased productivity and organizational commitment. If job satisfaction is not obtained by employees, it will reduce productivity, one of which is the employees of the Padang Pariaman Regency Ministry of Religion office, based on the results of a pre-survey regarding employee job satisfaction, it is concluded that they do not have satisfaction with their work, which can reduce productivity and organizational commitment. This study aims to see the effect of Extrinsic Motivation, Colleague Support and Religiosity on Job Satisfaction of Employees at the Office of the Ministry of Religion, Padang Pariaman Regency. The method used in this research is quantitative research with a descriptive approach. The population in this study were all employees of the Office of the Ministry of Religion of Padang Pariaman Regency as many as 62 people using multiple linear regression tests. The results of this study indicate that extrinsic motivation, coworker support and religiosity have a positive and significant impact on job satisfaction of employees of the Office of the Ministry of Religion, Padang Pariaman Regency.